Review of Sesioctonus Viereck (Hymenoptera: Braconidae: Agathidinae) from Colombia with descriptions of five new species - Sharkey, Michael J.; Briceño G., Rosa A. (Zootaxa, 2005)
As part of an extensive survey of Colombian arthropods, the species of Sesioctonus from Colombia are reviewed. Nine new Colombian species records for Sesioctonus are reported, including five new species that are described here. The species identified are Sesioctonus diazi Briceño, S. galeos Briceño, S. theskelos Briceño, S. grandis Briceño, S. boliviensis Briceño, Sesioctonus longinoi n.sp., Sesioctonus philipi n.sp., Sesioctonus torresi n.sp., Sesioctonus stephaniai n.sp., and Sesioctonus susanai n.sp. Including the species reported here, eleven species of Sesioctonus are recorded from Colombia. A revised key to all known species of Sesioctonus is presented.